Iklim Organisasi sebagai Moderator antara Goal Orientation terhadap Organizational Withdrawal Behavior - Tasya Augustiya; Tahrir Tahrir; Ambar Sulianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to examine how organizational climate can moderate the effect of goal orientation on organizational withdrawal behavior (OWB). The research design used causality quantitative method. The sampling technique used population with the total of 207 members of Student Press in a university in Bandung. The data collection used a set of questionnaire consists of Organizational Withdrawal Behavior Scale, Goal Orientation Scale, and Organizational Climate Questionnaire. The data analysis used PROCESS Moderation Model test. The results show that goal orientation affect organizational withdrawal behavior significantly and organizational climate can moderate the effect. This finding indicate that organizational climate has a significant role to improve goal orientation on organizational withdrawal behavior.